OPTIMASI PENCARIAN RUTE TERPENDEK PADA OBJEK WISATA CAMPING GROUND BATU TAPAK CIDAHU DENGAN METODE ALGORITMA GREEDY - Siti Halimah; Ade Momon S (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
Location is an important factor in tourist attractions. Strategic and easy-to-reach road access is a factor in tourists' decisions about tourism. In this research, researchers focused on finding the shortest route to the Camping Ground Batu Tapak tourist attraction in Cidahu, Sukabumi Regency, where tourists still have limited shortest routes to the tourist attraction. This research aims to determine the fastest route to the Batu Tapak Camping Ground tourist location to create effective and efficient route optimization. The method used in this research is the greedy algorithm, namely an algorithm that has an optimal solution by finding the shortest route. There are two routes with different distances, requiring researchers to use the Greedy Algorithm method with the result that route 2 is the shortest route to the Batu Tapak Camping Ground tourist attraction with a distance of 10.45 km.